Perlindungan Konsumen Dalam Praktik Jual Beli Bahan Bakar Minyak (BBM) Menggunakan Mesin Pertamini di Kota Masohi - Muhammad Rizal Muhari; Teng Berlianty; Theresia Louize Pesulima (PATTIMURA Law Study Review, 2023)
ABSTRACT: Every year the number of vehicles in Indonesia continues to grow as a result of human needs in using fuel oil (BBM) is very large and continues to increase, therefore to meet the need for fuel the government issued Law No. 22 of 2001 concerning Oil and Gas. The purpose of this study are to know and explain the responsibility of business actors for the sale of pertamini (fuel) that does not match the dose, to know and explain how to resolve disputes if consumers experience losses. The method used in this research is normative juridical with statute approach and conceptual approach. The legal materials used are primary, secondary legal materials which are analyzed qualitatively. The results of this study indicate that the form of responsibility of pertamini business actors is responsibility in the form of product liability where Pertamini business actors have the responsibility to provide guarantees for consumer rights, in terms of providing compensation, refueling through digital pertamini, pertamini business actors are obliged to provide compensation or compensation in the form of a refund of the amount of dose that has been harmed, as well as the return of the amount of dose owned by consumers of the same value before the shortage in the value of the dose that causes harm to consumers. Settlement of disputes filed by consumers can be resolved in two ways, namely by taking court channels or taking out-of-court channels. The Consumer Protection Law gives freedom to consumers who feel harmed to sue business actors through the courts, but if consumers want to settle disputes with business actors outside the courts, the Consumer Protection Law provides the Consumer Dispute Resolution Agency (BPSK) which has the authority to handle disputes related to these consumers.